Minimally Invasive Aortic Valve Replacement with Partial Lower Sternotomy - Morimoto, Keisuke; Miyasaka, Shigeto; Shiraya, Suguru; Kobayashi, Futoshi (Scientific Research, 2018)
Objectives: Due to recent spread of minimally invasive surgery, the demand for minimally invasive cardiac surgery (MICS) is increasing. We investigate the usefulness of minimally invasive aortic valve replacement (MICS-AVR) which was performed in our hospital. Methods: Of 63 consecutive patients undergone an isolated aortic valve replacement (AVR), 16 patients underwent MICS-AVR with partial lower sternotomy (M group) and 47 patients underwent AVR with median full sternotomy (C group). We compared the two groups in a retrospective study. Results: No significant difference was found in the surgical and perioperative-related factors between the two groups. However, the average of aortic cross-clamping time was longer, and intensive and high care unit stay was shorter in the M group. A tendency to decrease blood transfusion was observed in the M group. There was no hospital death in all patients. The mean follow-up period was 29 ± 15 months. There was no significant difference between the two groups in the survival rate, and the 5-year survival rates were 88.9% in the M group and 85.9% in the C group. Conclusion: It was suggested that the MICS-AVR could be safe and useful procedure in AVR.
Keywords: Minimally Invasive Cardiac Surgery (MICS); Aortic Valve Replacement (AVR); Partial Sternotomy